Tractor path overlap is influenced by field shape and terrain attributes - Tulsi P. Kharel; Phillip R. Owens; Amanda J. Ashworth (Agricultural & Environmental Letters, 2020)
Abstract Tractor overlaps and gaps during field operations reduce production efficiencies; however, studies evaluating linkages between overlaps and field terrain attributes are limited. Our objective is to explore relationships between tractor guidance (TG) systems and field shape and terrain attributes on tractor path overlap. Fields with varying attributes were used for fertilizer (six fields) and herbicide (four fields) applications (with and without TG). Overlap polygon and terrain attributes were overlaid and sampled per 50‐ × 50‐m grid cell. Overlap increased with increasing field irregularities (6 to 11% field area), shorter pass lengths (2 to 19 m2), greater slope (17 to 53 m2), and roughness index (13 to 38 m2) per grid cell. Averaged across slope classes, overlap area decreased 41 to 17 m2 (58% reduction) per grid cell with TG. These results are important for future design of machinery, sensors, and improved TG efficiencies for automated field operations.